Penguatan Pendidikan Karakter Melalui Literasi Berbasis Kearifan Lokal - I Made Ari Winangun (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
The results of an educational process not only produce intelligent and skilled humans, but also people who have character. Therefore, it is necessary to develop character education. One concrete effort that can be implemented is literacy activities. Literacy is a activity including reading, writing, understanding, and communicating information in order to obtain the meaning and message contained in the information. Literacy that is carried out in an effort to improve character education is based on local wisdom literacy. This literacy can be done through several Balinese local wisdom products in the form of folklore, song art, as well as information on various religious holidays that are closely related to the values and order of life of the Balinese people. Through this activity, students 'interest in reading will increase because literacy activities are carried out close to students' daily lives. In addition, messages obtained in literacy activities will direct students to behave in a positive direction. Keywords: strengthening character education, literacy, local wisdom